Childhood cognitive development after fetal growth restriction. (25th March 2013) - Llurba, E.; Baschat, A. A.; Turan, O. M.; Harding, J.; McCowan, L. M.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2013:41:364–365 ABSTRACT: Objective: To examine the relationship between prenatal umbilical artery (UA) and internal carotid artery (ICA) Doppler findings and cognitive development at 3 and 6 years in low‐birth‐weight children. Methods: This was a study of 209 low‐birth‐weight (< 10 th centile) children born after 28 gestational weeks with UA resistance index (RI) measured within 2 weeks before delivery. Children with normal UA‐ and ICA‐RI were defined as small‐for‐gestational age (SGA) and those with abnormal UA or ICA Doppler findings as having fetal growth restriction (FGR). Cognitive ability at 3 and 6 years' corrected age was assessed using the fourth edition of the Stanford–Binet Intelligence Scale (SBIS) and compared between SGA and FGR groups. An SBIS score < 85 was considered to indicate delayed development. Results: The median gestational age at diagnosis of abnormal fetal growth was 36.6 (range, 28–41) weeks. There were 87 (41.6%) children classified as having FGR and 122 (58.4%) as SGA. The mean global SBIS score at 3 years was 109.4 (SD, 22.8) and at 6 years it was 110.5 (SD, 13.9). Overall, 22 (10.5%) children had delayed development at 3 years. Total SBIS scores and individual domain scores did not differ between FGR and SGA groups at 3 or 6 years and similar proportions in each group had delayed development. Conclusion: Abnormal prenatal UA and ICA Doppler findings are not associated with lower developmental scores in low‐birth‐weight children delivered in the third trimester of pregnancy. Copyright © 2013 ISUOG. Published by John Wiley & Sons, Ltd.